Analisis Organ Pembiayaan Rahn pada KSPPS BMT Lumbung Artho Jepara - Zuliani Sania Sholihatin (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2023)
This study aims to analyze the implementation of the rahn contract at KSPPS BMT Lumbung Artho Jepara. Rahn holds the property of one of the borrower's owners as a loan received. Rahn can also be interpreted as a mortgage or debt guarantee. The method used in this research is qualitative research. For this type of research using field research, namely by visiting sources directly to be interviewed about rahn financing. Data collection techniques carried out in this study were observation, interviews and documentation. The results of the interviews were recorded and then analyzed regarding the application of the rahn contract in financing. The implementation of the rahn contract is carried out through the rahn financing organ structure at KSPPS Lumbung Artho along with the marketing process. In the structure of the financing organ, the role of DPS (Sharia Supervisory Board) is outside the management staff. To facilitate marketing is carried out with promotion, communication and excellent service.